The glace : Bingsu / Nur Fazreen Nisha Lookman ...[et al.] - Lookman, Nur Fazreen Nisha; Dahalan, Siti Dazmenatasha; Mohamad, Nur Farah Amirah; Hasim, Khairoul Ikhwan; Ainuddin, Muhammad Thahir (2022)
The purpose of this business plan is to demonstrate entrepreneurial skills in preparing the business plan. First, a business idea needs to be chosen, whether selling products or providing services. Then, a business plan should be prepared as though the business is about to launch. All the main sections (administration, marketing, operations, and financial) that are necessary to start a business will be learned during the process of preparing and drafting the business plan. To complete the business plan, a five-person partnership has been formed. Every member of the partnership will be assigned to one of five positions: General Manager, Administrative Manager, Marketing Manager, Operational Manager, and Financial Manager. Each position has its own list of tasks and responsibilities, and each member needs to gain details pertaining their position. For instance, the General Manager is responsible in providing information on the business’s profile, nature of business, purposes, and backgrounds, among other things. Meanwhile, the Administrative Manager would oversee the details in the administrative side of things, and the Marketing Manager is in charge of the business’s marketing efforts. The Operational Manager, on the other hand, would oversee the business's daily operations, while the Financial Manager is in charge of the business’s finances. As a result, this business plan will consist of business backgrounds, Administrative Plan, Marketing Plan, Operation Plan, and Financial Plan. Apart from that, there will be a Business Model Canvas and a Partnership Agreement in this business plan. The Business Model Canvas is a strategic management template that is used to create new business models as well as document existing ones. It provides a visual chart that includes aspects that describe a business's or product's value proposition, infrastructure, customers, and finances, supporting businesses in aligning their activities by illustrating potential trade-offs. On the other hand, a Partnership Agreement is a legal contract that describes a partnership's management structure as well as the partners' rights, responsibilities, ownership interests, and profit distributions. A partnership agreement is not legally required, but it is strongly recommended to avoid problems among partners. Both Business Model Canvas and Partnership Agreement are included at the end of this business plan.